2006
DOI: 10.1002/dvdy.20905
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid is required for endodermal pouch morphogenesis and not for pharyngeal endoderm specification

Abstract: Because tissues from all three germ layers contribute to the pharyngeal arches, it is not surprising that all major signaling pathways are involved in their development. We focus on the role of retinoic acid (RA) signaling because it has been recognized for quite some time that alterations in this pathway lead to craniofacial malformations. Several studies exist that describe phenotypes observed upon RA perturbations in pharyngeal arch development; however, these studies did not address whether RA plays multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 94 publications
(126 reference statements)
1
67
0
Order By: Relevance
“…DEAB is an inhibitor of retinaldehyde, the enzyme that synthetizes retinoic acid, and can be used to deplete retinoic acid during embryogenesis (Kopinke et al, 2006). We observed that treating embryos with DEAB between 4 and 10 hpf leads to dramatic defects in the formation of the PLL system and of the inner ear.…”
Section: Origin Of the Primary And Secondary Placodesmentioning
confidence: 82%
See 1 more Smart Citation
“…DEAB is an inhibitor of retinaldehyde, the enzyme that synthetizes retinoic acid, and can be used to deplete retinoic acid during embryogenesis (Kopinke et al, 2006). We observed that treating embryos with DEAB between 4 and 10 hpf leads to dramatic defects in the formation of the PLL system and of the inner ear.…”
Section: Origin Of the Primary And Secondary Placodesmentioning
confidence: 82%
“…4-(Diethylamino) benzaldehyde (DEAB; Sigma-Aldrich) was used at 50 M (Kopinke et al, 2006) by dilution of a stock solution (50 mM in DMSO). Twelve fertilized eggs were placed in 6 ml of this solution at time t, transferred to 40 ml of system water at time t ϩ 2 h, and transferred a second time 15 min later.…”
Section: Methodsmentioning
confidence: 99%
“…In situ hybridization and immunohistochemistry was performed as previously described (Kopinke et al, 2006). The following in situ probes were used: axin2 (kind gift of R. Dorsky), dkk1 (gift from C. Houart), follistatin (Bauer et al, 1998), otx1 (Li et al, 1994), atoh7 (atoh7, (Kay et al, 2001), sox2 (Okuda et al, 2006), myca and cyclinD1 , pax6a (Krauss et al, 1991), stat3 (Krauss et al, 1991), her6 (Pasini et al, 2004), meis1 (Waskiewicz et al, 2001), vsx2 (Barabino et al, 1997 …”
Section: In Situ Hybridization and Immunohistochemistrymentioning
confidence: 99%
“…Previous data have suggested that RA is required for Dbx expression in other vertebrates (Pierani et al, 1999;Novitch et al, 2003). To block RA signaling in embryos, we used 4-(diethylamino)-benzaldehyde (DEAB), which has been shown to inhibit retinaldehyde dehydrogenase and subsequently the synthesis of RA (Perz-Edwards et al, 2001;Hamade et al, 2006;Kopinke et al, 2006). Embryos were treated with DEAB at 50% epiboly to test whether RA is required for the induction of Dbx expression.…”
Section: Ra Signaling Is Not Required For Induction Of Dbx Gene Exprementioning
confidence: 99%